1995
DOI: 10.1111/j.1601-0825.1995.tb00151.x
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral giant cell granuloma: a clinical study of 77 cases from 62 patients, and literature review

Abstract: OBJECTIVES: The aim of this study was to identify the principle clinical features of the peripheral giant cell granuloma (PGCG), and to recognise clinical features of PGCG that are poorly defined. DESIGN: We reviewed retrospectivety 77 cases of PGCG from 62 patients, from our files with respect to incidence, sex, patient age, race, clinical symptoms and signs, radio‐graphic features and recurrence following excision. RESULTS AND CONCLUSIONS: Our results were largety in agreement with previous reports, although… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
1
6

Year Published

2000
2000
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 28 publications
(37 reference statements)
4
45
1
6
Order By: Relevance
“…In the present study, PGCGs appeared more common in males, which is in contrast to the proved thesis that de-scribes predilection for female patients 3,9,11,[14][15][16] .Murat et al's also reported male predilection (56%) which was slightly higher than our results 17 . A mandible predominance (58.7%) was identified in our series, and is in agreement with other studies 4,9,14,17 .…”
Section: Resultscontrasting
confidence: 56%
“…In the present study, PGCGs appeared more common in males, which is in contrast to the proved thesis that de-scribes predilection for female patients 3,9,11,[14][15][16] .Murat et al's also reported male predilection (56%) which was slightly higher than our results 17 . A mandible predominance (58.7%) was identified in our series, and is in agreement with other studies 4,9,14,17 .…”
Section: Resultscontrasting
confidence: 56%
“…25 In humans, peripheral giant cell granulomas are located predominantly in mandibular gingiva. 13,15 Marginal excision was usually curative in this study, with recurrence reported in only 2 cases, each within 2 months after excision. No histologic features distinguished the peripheral giant cell granulomas that recurred from those that did not.…”
Section: Discussionmentioning
confidence: 99%
“…5 Although no sex predisposition for peripheral giant cell granulomas has been reported for dogs or cats, there is a slight female predominance in human cases. 13,15 Peripheral giant cell granulomas are most often in maxillary gingiva, similar to fibromatous epulis, and in contrast to acanthomatous ameloblastoma, for which 58.8% arise around mandibular canine teeth. 25 In humans, peripheral giant cell granulomas are located predominantly in mandibular gingiva.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,[15][16][17] Ancak, üç ça-lışmada alt ve üst çeneler arasında eşit dağılım gözlenmiştir. 6,10,18 Çene içi yerleşim açısından ço-ğunlukla alt çene posterior bölge rapor edilmiş-tir. 6,9,16,17 Mevcut çalışmada da en çok (%50) görülen çene içi yerleşim alt çene posterior bölge-dir ve bu açıdan literatür ile uyumluluk göster-mektedir.…”
Section: Gereç Ve Yöntemlerunclassified